Recognition of Gonadal Development in Eriocheir sinensis Based on the Impulse of Love at First Sight - Jiang, Jingjing; Su, Shengyan; Lai, Ting; Feng, Wenrong; Li, Feifan; Tian, Can; Gao, Yang; Munganga, Brian Peelekelo; Tang, Yongkai; Xu, Pao (Frontiers in Physiology, 2022)
Given the difficulty in identifying individuals with different degrees of ovarian development, we developed a new device utilizing the hypothesis mutual attraction behavior between male and female crabs with mature gonads by releasing the sexual pheromone can be examined. Ten female crabs were isolated from 40 in total in half an hour. Ovaries of crabs in isolated group were in stage IV, while those of the control groups were in stage III in histological analysis. In addition, progesterone (PROG) in experimental groups was significantly reduced compared with the control group (P<0.05), but no significant difference was detected in estradiol (E2). In response to the different developmental stage, hemolymph biochemical indices and determination of gonadal fatty acids profile were explored. The result indicated that nothing but C18:4 has the significant difference between these two groups. Transcriptome was conducted to know the genes involved in mutual attraction process, where differentially expressed genes (DEGs) were significantly related to gonadal development. Therefore, the device can be used to the isolation of Chinese mitten crabs with stage IV of ovary.